The Dynamics of Hadith Transmission in Basrah: A Critical Analysis of the Tadlis Phenomenon within the Structure of Ashahul Asanid - Mukhlis Mukhlis; Chairuddin Siregar (Diroyah : Jurnal Studi Ilmu Hadis, 2026)
This study aims to analyze the dynamics of hadith transmission in Basrah during the pre-canonical period (ca. 40–150 AH), focusing specifically on the paradox between Basrah's reputation as a center of Ashahul Asanid (the most authentic chains of transmission) and the prevalence of the tadlis phenomenon among its narrators. This temporal delimitation is strategically chosen to capture transmission interactions before the tradition was codified in the canonical compilations of the 3rd century AH, enabling a more accurate reconstruction of the formation of hadith authority. Basrah is known for possessing golden chains of narration highly relied upon by hadith scholars; however, it is also noted by critics as a region with a significant rate of tadlis practice. This research employs a qualitative method with a jarh wa ta'dil approach and historical-critical analysis to dissect how hadith scholars such as Imam Bukhari, Muslim, and Shu'bah ibn Hajjaj navigated the validity of narrations amidst the uncertainty of the mudallis' an'anah. The findings indicate that although tadlis was rampant among central Basrah figures like Qatadah and Hasan al-Basri, the integrity of Ashahul Asanid remained preserved through strict selection mechanisms, shawahid (corroborating evidence), and specific methods of tahammul. This article concludes that the phenomenon of tadlis in Basrah does not necessarily undermine the credibility of the region's chains of transmission but rather demands the application of a more layered and cautious methodology of isnad criticism compared to other narration centers.